2022
DOI: 10.3390/biom12050608
|View full text |Cite
|
Sign up to set email alerts
|

Star Polymers as Non-Viral Carriers for Apoptosis Induction

Abstract: Apoptosis is a widely controlled, programmed cell death, defects in which are the source of various diseases such as neurodegenerative diseases as well as cancer. The use of apoptosis in the therapy of various human diseases is of increasing interest, and the analysis of the factors involved in its regulation is valuable in designing specific carriers capable of targeting cell death. Highly efficient and precisely controlled delivery of genetic material by low-toxic carriers is one of the most important challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…When dispersed in aqueous media, copolymers selfassemble in different structures, such as micelles [5], vesicles [6,7], worms [8], etc., depending on their amphiphilicity, degree of polymerization, and architecture. In this way, they can act as nano reservoirs to encapsulate hydrophobic molecules [9] and/or complexes with hydrophilic (bio)macromolecules [10,11]. Careful choice of monomers can also lead to environmentally stimuli-responsive structures that can be further utilized for smart delivery and release of therapeutic molecules [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…When dispersed in aqueous media, copolymers selfassemble in different structures, such as micelles [5], vesicles [6,7], worms [8], etc., depending on their amphiphilicity, degree of polymerization, and architecture. In this way, they can act as nano reservoirs to encapsulate hydrophobic molecules [9] and/or complexes with hydrophilic (bio)macromolecules [10,11]. Careful choice of monomers can also lead to environmentally stimuli-responsive structures that can be further utilized for smart delivery and release of therapeutic molecules [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have demonstrated that polyplexes formed by stars with nucleic acids exhibited higher transfection efficacy than their linear counterparts ( Shim et al, 2008 ; Dai et al, 2010 ; Alhoranta et al, 2011 ; Zheng et al, 2013 ). Star polymers were used in prokaryote transformation ( Souza et al, 2021 ) and transfection of the eukaryotic non-human like COS-1 ( Dai et al, 2010 ; Zhou et al, 2007 ) and human cell lines such as HT-1080, HMEC, BdEC and others ( Xu et al, 2009 ; Fus-Kujawa et al, 2020 ; Fus-Kujawa et al, 2022 ). Their use as gene delivery vectors has also included gene silencing ( Mori et al, 2009 ; Boyer et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%